Pancreatic Exocrine Insufficiency in Chronic Diarrhea - Marcellus Simadibrata; Daldiyono Hardjodisastro; Abdul Aziz Rani (The Indonesian Society for Digestive Endoscopy, 2005)
Background: One of the causes of chronic diarrhea is pancreatic exocrine insufficiency. Chronic diarrhea cases are commonly encountered in Indonesia. Materials methods: All patients with chronic diarrhea at hospitals in Jakarta were included in this study and dyspeptic patients were used as control subjects. The study and control subjects must submit their stool for fecal pancreatic elastase-1 examination at a private laboratory in Jakarta. Mild/moderate pancreatic exocrine insufficiency was defined if the concentration was between 100 - 200 mg E1/g stool. Severe pancreatic exocrine insufficiency was defined if the concentration was below 100 mg E1/g stool. The data was analyzed using Fisher or Kruskal-Wallis tests. Results: There were 32 chronic diarrhea patients with a male to female ratio of 19/13 (59.38%/40.62%). The most frequent age range was 50-59 years old (39.5%). The characteristics (sex, age and race) of chronic diarrhea patients were matched with the characteristics of dyspeptic patients as control subjects (p 0.05). The fecal elastase-1 results in chronic diarrhea displayed greater pancreatic exocrine insufficiency ( 200 mg E1/g stool) than in dyspepsia (control) ( 200 mg E1/g stool, p 0.001). The mean fecal elastase-1 Result in chronic diarrhea and in dyspepsia were 316.29 + 195.44 vs. 475.93 + 65.33 mg E1/g stool (p 0.001). Six patients (18.74%) were established as having severe pancreatic exocrine insufficiency. Seven patients (21.88%) were found with mild/moderate pancreatic exocrine insufficiency. Conclusion: Pancreatic exocrine insufficiency was found frequently in chronic diarrhea Keywords: pancreatic exocrine insufficiency, chronic diarrhea, fecal pancreatic elastase-1